El estrés laboral y su influencia en el desempeño de los trabajadores de la Municipalidad Distrital de San Pedro de Lloc - Año 2016 - Isla Amaya, Dalva Rosely (2016)
The present research work aims to determine whether there is a direct relationship between work stress and performance of workers of the municipality district of San Pedro de Lloc. The research problem is referred to the following question: would of how influence occupational stress in the performance of workers of the municipality district of San Pedro de Lloc - year 2017?, which hypothesis is: the job stress affects negatively the performance of the workers of the district municipality of San Pedro de Lloc year - 2017., highlighting as study variables: Independent variable: work-related stress; and the dependent variable: performance of the workers. The design of transverse descriptive investigation, as well as inductive methods; analytical, statistical and research data collection, as the survey technique. Through studies in Municipality district de San Pedro de Lloc it can be concluded that: employees of the district municipality of San Pedro de Lloc suffer from work-related stress, and this is a key indicator for the performance of the workers. Does not have a training plan, assessment, employee motivational. There is discouragement in workers by the lack of recognition to his work by managers. Communication systems which are currently applied in the company are formal and maintaining hierarchical style which prevents strengthening linkages between managers and workers.